Groundwater and soil remediation process design and cost estimating of proven technologies - Hyman, Marve 1930; Dupont, R. Ryan (ASCE Press, 2001)
Explaining the design and costs of conventional treatment technologies, this book emphasizes the integration of remediation technologies into a process design scheme. Written chiefly for engineers, it describes the application of chemical engineering techniques to civil and environmental engineering and hydrogeologic contamination problems. Each step in process design and process control is outlined for a variety of remediation techniques, and applications of cost-estimation methods are described. Hyman teaches chemical engineering at the University of California, Berkeley. Dupont teaches environmental engineering at Utah State University, Logan. c. Book News Inc.